Reference materials produced for a European metrological research project focussing on measurements of NORM. (August 2017) - Larijani, C.; Pearce, A.K.; Regan, P.H.; Russell, B.C.; Jerome, S.M.; Crespo, M.T.; de Felice, P.; Lutter, G.; Maringer, F.; Mazánová, M.
Abstract: Reliable measurement of Naturally Occurring Radioactive Materials is of significance in order to comply with environmental regulations and for radiological protection purposes. This paper discusses the standardisation of three reference materials, namely sand, tuff and TiO2 to serve as quality control materials for traceability, method validation and instrument calibration. The sample preparation, material characterization via γ, α and Inductively Coupled Plasma Mass Spectrometry (ICP-MS) and the assignment of values for both the 4n (Thorium ) and 4n+2 (Uranium ) decay series are described. Highlights: Reliable measurement of Naturally Occurring Radioactive Materials. Standardisation of three reference materials, sand, tuff and TiO2 . NORM radiochemical analysis. Measurement of NORM by γ, α and mass spectrometry.